CRISPR/Cas12a-based approaches for efficient and accurate detection of Phytophthora ramorum - Guo, Yufang; Xia, Hongming; Dai, Tingting; Liu, Tingli; Shamoun, Simon Francis; CuiPing, Wu (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Phytophthora ramorum is a quarantine pathogen that causes leaf blight and shoot dieback of the crown, bark cankers and death on a number of both ornamental and forest trees, especially in North America and northern Europe, where it has produced severe outbreaks. Symptoms caused by P. ramorum can be confused with those by other Phytophthora and fungal species. Early and accurate detection of the causal pathogen P. ramorum is crucial for effective prevention and control of Sudden Oak Death. Methods In this study, we developed a P. ramorum detection technique based on a combination of recombinase polymerase amplification (RPA) with CRISPR/Cas12a technology (termed RPACRISPR/ Cas12a). Results This novel method can be utilized for the molecular identification of P. ramorum under UV light and readout coming from fluorophores, and can specifically detect P. ramorum at DNA concentrations as low as 100 pg within 25 min at 37°C. Discussion We have developed a simple, rapid, sensitive, unaided-eye visualization, RPA CRISPR/Cas12a-based detection system for the molecular identification of P. ramorum that does not require technical expertise or expensive ancillary equipment. And this system is sensitive for both standard laboratory samples and samples from the field.